Psychological Capital and Quality of Life Among Secondary School Tutors in Kwara State Nigeria - Olanrewaju, Muraina Kamilu; Tinuke, Kamaldeen Rahmat (Journal of Psychological Perspective, 2022)
The present study attempts to explore the relationship between psychological capital and the quality of life among secondary school tutors in Kwara State. The study adopted a descriptive design of ex-post-facto type. Multi-stage sampling technique was to select 420 participants from 6 local government areas in Kwara State. The variables were measured using a validated instrument with a reliability coefficient of 0.81. The data were analyzed using Pearson Product Moment Correlation and regression at 0.05 level of significance. The result confirmed that there was a correlation between hope and resilience and quality of life. The results indicated that hope and resilience had a relationship with quality of life. Therefore psychological capital increases the quality of life of the tutors in Kwara State. Therefore, based on the findings, it was recommended that counselling psychologists should intensify their effort to arrange conferences for educational stakeholders on the effects of positive psychological capital on quality of life. The implication of this is that psychological capital contributed to the quality of life and as such counselling psychologists should create more awareness towards enhancing the quality of life among secondary school tutors in Kwara State.